An organisation development intervention in a rural school in the Omusati region of Namibia - Perestrelo, Helena Ndeyatila (Rhodes University, Faculty of Education, Department of Education, 2008)
Organizations globally are challenged with a very volatile, fast changing environment. It is only those organizations that develop the capacity to change timeously that will survive in this millennium. (Meyer & Botha, 2000, p.23) Organizational development (OD) is a planned change approach aimed at changing behaviour and enhancing organizational effectiveness. Central to such an approach is continuous business process improvement. OD rests on the foundation of values and assumptions about people and organizations, and it is imperative that organizations adopt systematic methodologies in introducing business improvement interventions. The study introduced an OD approach to one of the rural primary schools in the Omusati region of Namibia, with the purpose of examining if it would bring change in the school. My goal was to explore participants' experience and perception of the OD process and to investigate the possible short term outcome of such an intervention. The case study involved 16 staff members made up of a principal, one head of department and 14 teachers. Data was gathered through formal interviews with the principal, head of department and three teachers, through a focus group interview with teachers, and through observation and observation note entries. The study found that OD was a new concept approach to the participants which differs completely from the way that change processes are introduced in the schools. Participants felt that introducing change in an organization using an OD approach can bring effective change, but it can also place huge demands on participants' commitment. This is particularly so if they do not adopt it as an internal process of business improvement. The OD approach is a long-term change process and not a quick fix. Finally, the outcome of the intervention indicated enthusiasm for the school to continue addressing the prevailing challenges despite various obstacles that they do not have control over.
Keywords: Rural schools -- Namibia -- Omusati; Organizational change -- Namibia -- Omusati; School management and organization -- Namibia -- Omusati; Educational change -- Namibia -- Omusati; School improvement programs -- Namibia -- Omusati